2007
DOI: 10.1021/jp072404k
|View full text |Cite
|
Sign up to set email alerts
|

Multicomponent Diffusion of Lysozyme in Aqueous Calcium Chloride. The Role of Common-Ion Effects and Protein−Salt Preferential Interactions

Abstract: To investigate the effect of calcium salts on the thermodynamic and transport properties of aqueous solutions of proteins, we report ternary diffusion coefficients for the lysozyme-CaCl 2 -water ternary system at 25°C and pH 4.5. We have used our ternary diffusion coefficients to calculate preferential-interaction coefficients as a function of salt concentration. This has allowed us to characterize protein-salt thermodynamic interactions. We have observed the presence of large common-ion effects by examining t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
31
0

Year Published

2008
2008
2021
2021

Publication Types

Select...
8
1

Relationship

4
5

Authors

Journals

citations
Cited by 13 publications
(31 citation statements)
references
References 40 publications
0
31
0
Order By: Relevance
“…A similar expression can be also derived for (D 32 Effect of Cross-Diffusion on Protein Crystallization. The effect of cross-diffusion coefficients on protein crystallization processes has been examined in model calculations.…”
Section: Resultsmentioning
confidence: 96%
See 1 more Smart Citation
“…A similar expression can be also derived for (D 32 Effect of Cross-Diffusion on Protein Crystallization. The effect of cross-diffusion coefficients on protein crystallization processes has been examined in model calculations.…”
Section: Resultsmentioning
confidence: 96%
“…23,[29][30][31][32][33][34] Diffusion measurements at 25°C on lysozymesalt-water 31,32 and lysozyme-poly(ethylene glycol)-water 33,34 by optical interferometry have shown that cross-diffusion terms…”
Section: Introductionmentioning
confidence: 99%
“…The presences of neutral salts [50][51][52][53] showed a marked shift in phase transitions. It has been suggested that the protein unfolds in the cooperative binding region [54] and sodium chloride is reported to act as a denaturing agent in many protein systems [55][56][57]. According to Curtis et al [58] in classical salting-out behavior, the protein-salt preferential interaction is unfavorable as addition of salt raises the surface free energy of the protein, thereby protein-protein attraction increases leading to a reduction in solubility.…”
Section: Introductionmentioning
confidence: 99%
“…[1][2][3] Macromolecule-osmolyte thermodynamic interactions are also central for understanding diffusive mass transport of macromolecules. [9][10][11][12][13] Indeed a gradient of osmolyte concentration can generate a gradient of macromolecule chemical potential and vice versa. This is responsible for coupled diffusion in systems with two or more solutes.…”
Section: Introductionmentioning
confidence: 99%